The Effect of Servant Leadership on Employee Creativity with Employee Engagement and Employee Resilience as Mediation - Irawati, Yeyen; Anindita, Rina (Jurnal Diversita, 2025)
This study aims to examine the effect of servant leadership on employee creativity, employee engagement and employee resilience in commuting female workers in private companies. As well as evaluating the mediating role of employee engagement and employee resilience on the relationship between servant leadership and employee creativity. Using purposive sampling method, and distributing online questionnaires, to female workers in private companies in the period March to May 2024. Respondents were collected as many as 154 people who had a distance to work of more than 20 km and used public transportation. Data were analyzed using the Structural Equation Model (SEM). The results showed that servant leadership has a positive effect on employee creativity and employee resilience. besides that employee resilience has a positive effect on employee engagement and employee creativity. these findings also show that employee engagement has a positive effect on employee creativity. And Employee resilience and Employee engagement mediate the effects of Servant leadership and employee creativity. The managerial implications of this study emphasize the importance of developing servant leadership and employee resilience to increase engagement and creativity in the workplace. The limitation of this study is the generalization of results that are limited to female employees only. Future research is recommended to explore other variables that affect servant leadership, employee engagement, and employee creativity.